Faktor yang Berpengaruh terhadap Penyembuhan Luka Perineum pada Ibu Postpartum - Apri Sulistianingsih; Yossy Wijayanti (Universitas STRADA Indonesia, 2019)
Most of women who has vaginal delivery is risky of perineum laceration even from spontaneous tears or episiotomy. Perineum laceration can effect of many complication that cause morbidity and mortality. This study to analyze the analysis of Factors Affecting The Healing Of Perineal Wounds in Post Partum Mother. The design was used observational analytic with cross sectional approach. The population of this study was postpartum mothers with second degree perineal laceration. There were 120 participant selected in this study. This study was located in Primary health care area in Pringsewu Lampung Indonesia. Statistic analysis used chi square and multiple logistic regression. The findings indicate that factors affecting of perineal wound healing significant are education, food abstinence, Types of suture, Knowledge of perineum care, Perineum Care, Drug rececption and Types of Laceration. The most dominant factor is food abstinent.